Assessment of Body Weight Changes in Patients with Inflammatory Bowel Diseases Initiating Biologic Therapy: A Prospective Cohort Study - Borren, Nienke Z.; Tan, William; Jess, Alison T.; Li, Pei-Hsuan Mimi; Garber, John J.; Luther, Jay; Colizzo, Francis P.; Khalili, Hamed; Ananthakrishnan, Ashwin N. (Digestive diseases and sciences, 2020)
Background Prior studies have inconsistently suggested that biologic therapy may be associated with weight gain in inflammatory bowel disease patients (IBD). Our aim was to compare weight gain across different biologic therapy classes with distinct mechanisms of action. Methods This prospective cohort study recruited patients with moderate to severe IBD initiating outpatient biologic therapy with anti-TNF (infliximab, adalimumab), vedolizumab, or ustekinumab. Weight measurements were performed at weeks 0, 14, 30, and 54. Changes in weight between baseline and each of the follow-up visits were modeled as a continuous variable, and multivariate regression assessed the independent effect of therapeutic class on this outcome. Results Our study enrolled 269 patients (163 CD, 106 UC) initiating biologic therapy [99 anti-TNF (37%), 122 vedolizumab (45%), 48 ustekinumab (18%)]. From baseline, the weight significantly increased at week 14 with a mean of 0.36 kg (± 3.8 kg, p = 0.004) and continued to increase compared to baseline with 0.96 kg (± 3.9 kg, p < 0.001) and 1.29 kg (± 4.2 kg, p < 0.001) at week 30 and 54, respectively. On univariate and multivariable analysis, no significant differences between any of the biologic therapies for weight gain were seen at any time point (weight gain anti-TNF: 0.31 kg, 1.06 kg, 1.33 kg; VDZ: 0.30 kg, 0.83 kg, 1.10 kg; UST: 0.63 kg, 1.21 kg, 2.31 kg at wk 14, wk 30, and wk 54, respectively). None of the disease activity parameters showed any statistical association with weight gain. Conclusion There was no difference in weight gain among the different biologic therapeutic classes.